Microbiota extremofila and environmental resistomas of the thermal spring “Thermal baths La Merced” Quito-Ecuador - Medina Ramírez, Gerardo (2016)
The thermal waters are not sterile they possess a microbiota reflecting their physicochemical extreme characteristics. There is evidence that this microbiota may be the reservoir of antibiotic resistance genes, termed environmental resistomas. Therefore, the objective of the present work was to study the water bacterial microbiota of the Termas la Merced Spa, located near the City of Quito, Ecuador, to isolate the bacteria and determine the resistance patterns to antibiotics. Thermal water samples were collected from both the emergency area and the swimming pools used by bathers for a period of 6 months between July and December 2015. The isolate of the mesophilic aerobic bacteria using the Petrifilm ™ plates. Identification of bacterial colonies was performed according to the tests suggested by MacFaddin (2003) and Barrow and Feltham (1993), supplemented with MicrogenTM bacterial identification tests. Antibiotic susceptibility profiles were performed using the Kirby Bauer method. A total of 13 bacterial clones corresponding to Brevundimonas diminuta, Aeromonas schubertii, Budvicia aquatica, Acinetobacter haemolyticus, Bacillus spp, Citrobacter amalonaticus, Pseudomonas stutzeri and Xenorhabdus beddingii were identified. All isolates showed resistance to at least one antibiotic. The highest number of resistance (4 antibiotics) was exhibited by Brevundimonas diminuta strains. All isolates showed resistance to Cephalothin. It is demonstrated that these waters possess a characteristic microbiota and the presence of environmental resistomas.